Operational Landscapes: Hinterlands of the Capitalocene. (2nd January 2020) - Brenner, Neil; Katsikis, Nikos
Abstract: In recent decades, the field of urban studies has neglected the question of the hinterland: the city's complex, changing relations to the diverse noncity landscapes that support urban life. Neil Brenner and Nikos Katsikis of the Urban Theory Lab at the Harvard Graduate School of Design argue that this 'hinterland question' remains essential, but must also be radically reimagined under contemporary conditions.